Granulomatosis with Polyangiitis in Adolescence: Two Distinct Presentations - Rafael Figueiredo; Inês Pires Duro; António Marinho; Conceição Mota; Margarida Guedes; Carla Zilhão (Case Reports in Rheumatology)
Introduction. Granulomatosis with polyangiitis (GPA) is a rare disease in pediatric age. We report two cases with distinct presentations. Case Reports. A seventeen-year-old male with prolonged febrile syndrome, cough, and constitutional symptoms. CT-scan showed cavitated lesions of the lung and bronchial biopsy a necrotizing inflammatory process. The remaining investigation revealed hematoproteinuria and positive C-ANCA and anti-PR3. Complications: Bilateral acute pulmonary thromboembolism, splenic infarction, and extensive popliteal and superficial femoral deep vein thrombosis. He was treated with corticosteroids, immunoglobulin, rituximab, and anticoagulation. Rituximab was maintained every six months during the first two years. Control angio-CT was performed with almost complete resolution of previous findings. In a twelve-year-old female with inflammatory signs of the limbs, investigation showed myositis of the thigh and tenosynovitis of the wrist, normocytic normochromic anemia (Hg 9.4 g/dL), mild elevation of inflammatory markers, and high creatine kinase. During hospitalization, she presented an extensive alveolar hemorrhage associated with severe anemia and positive C-ANCA and anti-PR3. Clinical deterioration prompted intravenous methylprednisolone pulses and plasmapheresis. Induction therapy with rituximab and prednisolone showed good results. Rituximab was maintained every six months, for 18 months, with gradual tapering of corticoids. Discussion. GPA is a systemic disease with variable clinical presentation and severity. Pediatric patients have similar clinical manifestations to adults but different frequencies of organ involvement; constitutional symptoms are also more common. We highlight the different presentation of these two cases, as well as the need for an individualized approach. Rituximab has been used for both induction-remission and maintenance therapy, with good results, particularly in young patients.